Epidemiology of Kawasaki disease before and after universal Bacille Calmette‐Guérin vaccination program was discontinued. (3rd October 2019) - Pasma, Hanna; Honkila, Minna; Pokka, Tytti; Renko, Marjo; Salo, Eeva; Tapiainen, Terhi
Abstract: Aim: Bacille Calmette‐Guérin (BCG) vaccine (BCG) has been suggested to induce the primary immunity needed for the subsequent Kawasaki disease (KD). We studied the epidemiology of KD before and after the universal BCG vaccination ended in Finland in September 2006. Methods: Kawasaki disease cases were retrieved from national health registries from 1996 to 2016 for annual incidence rates. We then compared 612 433 children born in the BCG vaccination era, from 1 January 1996 to 30 August 2006, to 604 163 born after BCG era, from 1 September 2006 to 31 December 2016. Results: The annual incidence rates did not change after the BCG vaccination stopped. We found 370 first visits for KD by children born in the BCG era and 341 after universal BCG vaccination ended. The mean age at diagnosis increased from 2.6 years to 3.0 years (95% CI−0.64 to −0.012, P  = .04) and the proportion of children with Kawasaki disease under 5 years decreased from 87% to 81% (95% CI 1%‐12%, P  = .02). Conclusion: Discontinuing the universal BCG vaccination programme did not change the incidence rates of KD. The increased age at diagnosis could suggest that the pathogenesis of KD may be associated with the immunological pathways primed by BCG immunisation.